Banking and finance in Japan : an introduction to the Tokyo market - Tatewaki, Kazuo, 1935- (London ; New York : Routledge, 1991)
Financial structure and deregulation. Financial markets. Financial institutions. Monetary authorities and monetary policy.
Keywords: Finance; Economics; Japan; Banks; Monetary policy; Banks and banking -- Japan; Banks and banking -- Deregulation -- Japan; Financial institutions -- Japan; Monetary policy -- Japan